2014
DOI: 10.1128/iai.01652-14
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Associated Urinary Tract Infection by Pseudomonas aeruginosa Is Mediated by Exopolysaccharide-Independent Biofilms

Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen that is especially adept at forming surface-associated biofilms. P. aeruginosa causes catheter-associated urinary tract infections (CAUTIs) through biofilm formation on the surface of indwelling catheters. P. aeruginosa encodes three extracellular polysaccharides, PEL, PSL, and alginate, and utilizes the PEL and PSL polysaccharides to form biofilms in vitro; however, the requirement of these polysaccharides during in vivo infections is not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 51 publications
3
135
0
Order By: Relevance
“…Second, the ⌬fliC strain was able to cause CAUTI similarly to PA14. Since mutations in the exopolysaccharides (29), flagella, and type IV pili are not required for P. aeruginosa to cause CAUTI, the c-di-GMP-regulated process that contributes to CAUTI is likely through an unknown mechanism that is likely specific to the urinary tract. Furthermore, the moderate reduction in bacterial burden for any of the single mutants with mutations in genes encoding DGC and PDE suggests that there is functional redundancy of DGCs in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the ⌬fliC strain was able to cause CAUTI similarly to PA14. Since mutations in the exopolysaccharides (29), flagella, and type IV pili are not required for P. aeruginosa to cause CAUTI, the c-di-GMP-regulated process that contributes to CAUTI is likely through an unknown mechanism that is likely specific to the urinary tract. Furthermore, the moderate reduction in bacterial burden for any of the single mutants with mutations in genes encoding DGC and PDE suggests that there is functional redundancy of DGCs in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data indicated that P. aeruginosa formed biofilms during the murine model of CAUTI independently of the Pel and Psl exopolysaccharides (29). Here we tested whether the c-di-GMP signaling pathway, which also regulates P. aeruginosa biofilm formation in vitro, participates during CAUTI.…”
Section: C-di-gmp Levels During Initial Infection Affect Colonizationmentioning
confidence: 92%
See 1 more Smart Citation
“…The number of cells per sample were enumerated at OD 600 = 0.6 and 2.0 for each strain by plating serial dilutions. The volume of one bacterium was estimated to be 4.3 × 10 −1 fL, assuming the bacterium to be cylindrical in shape with spherical poles having an average length of 1.5 and 0.65 μm in diameter based on SEM image analysis (80). The total c-di-GMP and pGpG extracted in each sample were3 then divided by the total intracellular volume of the cells in the sample to provide the intracellular concentration of each analyte.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the group of surface proteins called MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) is also major determinants of the initial bacterial attachment on tissues and biomaterials. P. aeruginosa produces three different exopolysaccharides (alginate, Psl and Pel) that participates in biofilm formation [58]. Alginates are composed of uronic acid and reduce the biofilm susceptibility to antibiotic and human defense [59].…”
Section: Bacterial Biofilm Productionmentioning
confidence: 99%